Spatial Correlates of Patients’ Travel Experience & Satisfaction in Hospital Outpatient Department - Khan, Nayma (ARCC Conference Repository, 2014)
Designing a physical environment that is safe, accessible and easy to use can significantlyimprove patients’ satisfaction and the quality of healthcare experience. Literature shows that difficulties in wayfinding cause delay in patients’ movement, together with loss of time, decreased safety, and increase environmental stress. However, less is known concerning how wayfinding difficulties affect patients’satisfaction and travel experience. In this research it is assumed that an easily accessible and visible spatiallayout may have direct or indirect positive effects on patients’ movement, travel time, and way finding; and, as a result, it may have positive effects on patients’ travel experience and satisfaction. The data was collected through systematic behavioral observation, patient survey, and floor layout analysis that included the measurement of actual route distance, travel distance, and spatial network distance using space syntax techniques. Findings of the study include the following: 1) patients’ satisfaction depends on age, number of visits, frequency of visits, signage system, overall layout, and design quality; 2) patients’ travel behavior is positively affected by route attributes; 3) overall patients’ satisfaction does not seem to have any relation with the patients’ travel behaviors and syntactic attributes of the layout; and 4) male and female patients’ satisfaction and travel behavior show different association with syntactic properties of the layout. It is hoped that the study will contribute to an improvement of the design of the spatial layout of the outpatient department so that patients may receive their services in the least amount of time without becoming lost or missing an appointment due to wayfinding problems; and an increase in patients’ satisfaction and travel experience.